2012
DOI: 10.1194/jlr.m020941
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of enzymes involved in ceramide biosynthesis causes distinct global alterations of lipid homeostasis and gene expression

Abstract: Dysregulation of ceramide synthesis has been associated with metabolic disorders such as atherosclerosis and diabetes. We examined the changes in lipid homeostasis and gene expression in Huh7 hepatocytes when the synthesis of ceramide is perturbed by knocking down serine pal mitoyltransferase subunits 1, 2, and 3 (SPTLC123) or dihydroceramide desaturase 1 (DEGS1). Although knocking down all SPTLC subunits is necessary to reduce total ceramides significantly, depleting DEGS1 is sufficient to produce a similar o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 59 publications
5
21
0
Order By: Relevance
“…In particular, 13’-COOHs caused rapid increase of dhCers but decrease of Cers including C 16:0 -Cer during short 2-h incubation, indicating that DEGS-catalyzed conversion of dhCers to Cers is compromised. The similar pattern of sphingolipid changes was reported in DEGS knockout model [34, 35]. Consistently, δT-13’-COOH inhibited DEGS enzyme activity in an in vitro assay despite having no impact on its protein expression.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In particular, 13’-COOHs caused rapid increase of dhCers but decrease of Cers including C 16:0 -Cer during short 2-h incubation, indicating that DEGS-catalyzed conversion of dhCers to Cers is compromised. The similar pattern of sphingolipid changes was reported in DEGS knockout model [34, 35]. Consistently, δT-13’-COOH inhibited DEGS enzyme activity in an in vitro assay despite having no impact on its protein expression.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, like 13’-COOHs, celecoxib (a selective COX-2 inhibitor) has recently been demonstrated to inhibit the DEGS activity and cause similar sphingolipid alterations in colon cancer cells [28]. It is noteworthy that downregulation of DEGS has been shown to cause profound changes of cell signaling, lipid homeostasis and gene expression [34, 35], which may contribute to the treatment effects (e.g. anti-proliferation) on cancer cells by these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…With enzyme assays and protein analysis, we have demonstrated that γTE inhibits cellular DEGS activity without affecting its protein expression. In agreement with inhibition of DEGS, γTE-caused changes of sphingolipids up to 8 h incubation are similar to those observed in DEGS1 knockout cells [36, 37]. Besides γTE, some cancer preventing agents have been shown to inhibit DEGS activity including resveratrol [18], celecoxib [38] and fenretinide [25].…”
Section: Discussionsupporting
confidence: 66%
“…The reaction carried out by SPT - the condensation of serine and palmitoyl CoA to produce dihydrosphingosine (dhSph) - has been shown to be a rate-limiting step in de novo sphingolipid biosynthesis21. Humans possess three variants of SPT (SPTLC1, SPTLC2, SPTLC3), and SNPs in all three have been found to be significantly associated with type 2 diabetes and related phenotypes22232425262728. Likewise, treatment with myriocin (a specific inhibitor of SPT) substantially reduces ceramide synthesis and ameliorates insulin resistance in diabetic rodents2930.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction of this enzyme removes the dhCer contribution from ceramide production, and an increase in DEGS promotes ceramide production. Recent work has shown that signaling targets of ceramide are not affected by similar levels of dhCer, which suggests that the enzyme DEGS is essential in cell regulation31 and plays a role on glucose homeostasis as well: multiple SNPs in DEGS are significantly associated with 2 hour glucose, mice lacking DEGS are resistant to dexamethasone-induced insulin resistance and DEGS-knockdown mice myoblast are protected from palmitate-induced ceramide-mediated insulin resistance22282932.…”
Section: Discussionmentioning
confidence: 99%